THE FLOTATION OF SOUTH AFRICAN CHROMITE ORES IN ACIDIC MEDIA - Yigit, Erdogan; Saridede, Muhlis Nezihi; Ozcimen, Didem (TANGER LTD, 2014)
Chromite is an important strategic mineral usually associated with other gangue minerals, mainly silicates. The selective flotation of chromite minerals of any chromite ore have some difficulties due to dissolved cations from gangue minerals. By this work, selective flotation of various chromite ores were studied to determine some of the features of flotation. Different chromite ores from South Africa were made flotation using the anionic collector, A825 (petroleum sulfonate), after conditioning with H2SO4 at low pH values in the range of 1 and 3. Chromite was separated as concentrate from the gangue successfully by using anionic collector at low pH values. Higher recovery ratios and higher separation index values were obtained at lower pH values. Longer conditioning time has positive effect on the recovery ratio of chromite in the concentrates and of silica in the tailings.
Keywords: Flotation; chromite ore; pH; anionic collector; separation index; Metallurgy & Metallurgical Engineering